"Prepared" fear or socio‐cultural learning? Fear conditioned to guns, snakes, and spiders is eliminated by instructed extinction in a within‐participant differential fear conditioning paradigm. (12th December 2019) - Luck, Camilla C.; Patterson, Rachel R.; Lipp, Ottmar V.
Abstract: Across three experiments, we investigated whether electrodermal responses conditioned to ontogenetic fear‐relevant (pointed guns) and phylogenetic fear‐relevant stimuli (snakes and spiders) would resist instructed extinction in a within‐participant differential fear conditioning paradigm. Instructed extinction involves informing participants before extinction that the unconditional stimulus (US) will no longer be presented. This manipulation has been shown to abolish fear conditioned to fear‐irrelevant conditional stimuli, but is said to leave fear conditioned to images of snakes and spiders intact. The latter finding, however, has only been demonstrated when fear‐relevance is manipulated between‐groups. It is also not known whether instructed extinction affects fear conditioned to ontogenetic fear‐relevant stimuli, such as pointed guns. In Experiment 1, we demonstrated that fear conditioned to images of pointed guns does not resist instructed extinction. In Experiment 2, we detected some evidence to suggest that fear conditioned to images of snakes and spiders survives instructed extinction but this evidence was not conclusive. In Experiment 3, we directly compared the effects of instructed extinction on fear conditioned to snakes and spiders and to guns and provide strong evidence that fear conditioned to both classes of stimuli is reduced after instructed extinction with no differences between ontogenetic and phylogenetic stimuli. The current results suggest that when fear relevance is manipulated within‐participants fear conditioned to both phylogenetic and ontogenetic, fear‐relevant stimuli responds to instructed extinction providing evidence in favor of a socio‐cultural explanation for "preparedness" effects. Abstract : Our research challenges Seligman's preparedness theory which proposes that humans are biologically predisposed to associate phylogenetic fear‐relevant stimuli with aversive outcomes. We provide strong evidence against the notion that prepared fear associations are "encapsulated from cognition" by demonstrating that fear conditioned to phylogenetic (snakes and spiders) and ontogenetic (pointed guns) fear‐relevant stimuli is immediately removed by instructed extinction.